1-[(Z)-2-Butyltellanyl-1-chloroethenyl]cyclohex-1-ene - Zukerman-Schpector, Julio; Caracelli, Ignez; Guadagnin, Rafael Carlos; Stefani, Hélio A.; Tiekink, Edward R.T. (International Union of Crystallography, 2012)
The Te II atom in the title mol-ecule, C 12H 19ClTe, is coordinated in a V-shaped geometry by C atoms derived from the disparate organic substituents. A short intramolecular C - H⋯Cl contact occurs owing to the proximity of the ethene bond in the six-membered ring to the Cl atom. In the crystal, mol-ecules assemble into layers parallel to the ac plane, with the closest inter-actions between them being of the Te⋯Te type [3.9993 (16) Å].